Long-term effects of glucocorticoids on function, quality of life, and survival in patients with Duchenne muscular dystrophy: a prospective cohort study. Issue 10119 (3rd February 2018) - McDonald, Craig M; Henricson, Erik K; Abresch, Richard T; Duong, Tina; Joyce, Nanette C; Hu, Fengming; Clemens, Paula R; Hoffman, Eric P; Cnaan, Avital; Gordish-Dressman, Heather; ,
Summary: Background: Glucocorticoid treatment is recommended as a standard of care in Duchenne muscular dystrophy; however, few studies have assessed the long-term benefits of this treatment. We examined the long-term effects of glucocorticoids on milestone-related disease progression across the lifespan and survival in patients with Duchenne muscular dystrophy. Methods: For this prospective cohort study, we enrolled male patients aged 2–28 years with Duchenne muscular dystrophy at 20 centres in nine countries. Patients were followed up for 10 years. We compared no glucocorticoid treatment or cumulative treatment duration of less than 1 month versus treatment of 1 year or longer with regard to progression of nine disease-related and clinically meaningful mobility and upper limb milestones. We used Kaplan-Meier analyses to compare glucocorticoid treatment groups for time to stand from supine of 5 s or longer and 10 s or longer, and loss of stand from supine, four-stair climb, ambulation, full overhead reach, hand-to-mouth function, and hand function. Risk of death was also assessed. This study is registered withClinicalTrials.gov, numberNCT00468832 . Findings: 440 patients were enrolled during two recruitment periods (2006–09 and 2012–16). Time to all disease progression milestone events was significantly longer in patients treated with glucocorticoids for 1 year or longer than in patients treated for less than 1 month or never treated (log-rank p<0·0001). Glucocorticoid treatment for 1 year or longer was associated with increased median age at loss of mobility milestones by 2·1–4·4 years and upper limb milestones by 2·8–8·0 years compared with treatment for less than 1 month. Deflazacort was associated with increased median age at loss of three milestones by 2·1–2·7 years in comparison with prednisone or prednisolone (log-rank p<0·012). 45 patients died during the 10-year follow-up. 39 (87%) of these deaths were attributable to Duchenne-related causes in patients with known duration of glucocorticoids usage. 28 (9%) deaths occurred in 311 patients treated with glucocorticoids for 1 year or longer compared with 11 (19%) deaths in 58 patients with no history of glucocorticoid use (odds ratio 0·47, 95% CI 0·22–1·00; p=0·0501). Interpretation: In patients with Duchenne muscular dystrophy, glucocorticoid treatment is associated with reduced risk of losing clinically meaningful mobility and upper limb disease progression milestones across the lifespan as well as reduced risk of death. Funding: US Department of Education/National Institute on Disability and Rehabilitation Research; US Department of Defense; National Institutes of Health/National Institute of Arthritis and Musculoskeletal and Skin Diseases; and Parent Project Muscular Dystrophy.